PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN DI BENGKEL ACHMAD MOTOR (BATURAJA) - Ahmad Hafizullah; Defrizal (Berajah Journal, 2026)
This research seeks to analyze the influence of service quality and corporate image on customer satisfaction at Achmad Motor Workshop. The study is grounded in the growing number of motorcycle users, which increases the demand for high-standard workshop services and a strong company image to foster customer loyalty. A quantitative method was applied, employing a random sampling technique involving 100 customers of Achmad Motor Workshop during the period of January 2 to 8, 2025. Data were gathered through questionnaires and analyzed through multiple linear regression. The results reveal that both service quality and corporate image significantly and positively impact customer satisfaction, both individually and collectively. The coefficient of determination (R²) value of 0.917 suggests that 91.7% of customer satisfaction variation is attributable to these two factors. It is evident that corporate image plays a more prominent role than service quality in enhancing customer satisfaction. These findings suggest that prioritizing brand image and consistently improving service delivery should be central to Achmad Motor Workshop’s growth strategy.